SP2 NPPG/RCPCH position statement: using standardised concentrations of unlicensed liquid medicines in children. How well has it been adopted nationally?. Issue 5 (20th April 2022) - Wignell, Andrew; Cooper, Helen; Duncan, Jennifer; Gill, Andrea
Abstract : Aim: In 2018, the Neonatal and Paediatric Pharmacists Group (NPPG) and Royal College of Paediatrics and Child Health (RCPCH) published a Position Statement recommending use of standard concentrations for 20 unlicensed medicines. The current version of this document contains recommendations for 12 of the original 20; the remainder having been removed due to introduction of licensed products. 1 This project aimed to assess the extent to which the current list has been adopted nationally, and to identify any barriers to its implementation. Method: A survey was developed using Microsoft Forms before email circulation to all NPPG members, asking them to share the survey with non-member colleagues who had been involved with local discussions and/or implementation of the recommendations. The survey was open for two weeks. Participants were asked if they were aware of the recommendations. Those who answered 'no' were asked no further questions; those answering 'yes' were asked to indicate if each of the 12 recommended concentrations was in use locally, and whether or not this was as a result of the publication. If a conscious decision had been taken not to adopt the concentration for a particular drug, respondents were asked to indicate if this was in favour of an alternative concentration, a non-liquid formulation or because the drug is not used locally. Multiple options could be selected for each drug. Respondents were then asked to detail any difficulties experienced in adopting the recommended concentration for particular drugs, or the list as a whole; and to suggest ideas which would support implementation if the list were to be extended in future. Results: 108 responses were received. 73 respondents (67.6%) were aware of the publication and provided feedback for the 12 recommended concentrations. Responses for a selected 4 of the 12 medicines were as follows: Spironolactone: 88.3% were using the recommended concentration; of those 24.4% reported adding it to a local formulary as a result of the list; 11.6% were unsure when it was added. Phenobarbital: 86.7% were using the recommended concentration; of those 19.3% reported adding it to a local formulary as a result of the list; 8.4% were unsure when it was added. Chloral Hydrate: 94.4% were using the recommended concentration; of those 11.1% reported adding it to a local formulary as a result of the list; 13.6% were unsure when it was added. Sodium Chloride: 72.8% were using the recommended concentration; of those 11.1% reported adding it to a local formulary as a result of the list; 11.1% were unsure when it was added. Common reasons given for not adopting a recommended concentration were a licensed product existing of a different concentration, or a different strength being more suitable for administration. Suggestions to aid implementation of future recommendations included ensuring dissemination to community-based practitioners, and providing clearer detail on the rationale behind choice of a concentration. Conclusion: The NPPG/RCPCH position statement has helped drive standardisation to some extent, though work is needed to understand how best to support practitioners implementing these and any future recommendations. Reference: Neonatal and Paediatric Pharmacists Group and Royal College of Paediatrics and Child Health, UK. Using Standardised Concentrations of Unlicensed Liquid Medicines in Children . April 2020. Available at: https://nppg.org.uk/wp-content/uploads/2020/04/NPPG-Position-Statement-18-01-V5-April-2020.pdf